Analysis of Students’ Errors in Solving Probability Problems Based on Kastolan’s Theory of Error Classification at Wesley Private Junior High School - Mastri Angely Sitanggang; Najwa Azzahra; Sevrianna Simarmata; Tiara Rezeki Simamora; Gavrila Nathania; Kairuddin . (Universitas Muhammadiyah Semarang, 2026)
This study aims to analyze student errors in solving probability problems based on the classification of errors according to Kastolan's theory, which includes conceptual, procedural, and technical errors. This study used a qualitative, descriptive approach. The subjects were 25 ninth-grade students at Wesley Private Junior High School who had studied probability. Data collection techniques were conducted through written tests and interviews. Data were analyzed through data reduction, data presentation, and conclusion drawing. The results showed that students still make various errors in solving probability problems, including errors in understanding basic concepts, inaccuracies in formulating solution steps, and calculation errors. Conceptual errors occur due to a lack of understanding of the definition and formula of probability, procedural errors are caused by a lack of systematic solution steps, while technical errors are caused by a lack of accuracy in calculations. These findings indicate that students' understanding of probability still needs to be improved. Therefore, more effective learning strategies are needed to minimize student errors in solving probability problems.